Factors Affecting Physical Growth in Children with Primary Vesicoureteral Reflux: A Single Center Experience - Rabia Miray Kışla Ekinci; Erkin Serdaroğlu (Galenos Yayinevi, 2019)
Aim:Primary Vesicoureteral reflux (VUR) is defined as retrograde urine flow from the bladder to the upper urinary system due to an insufficient valvular mechanism in the ureterovesical junction. We aimed to clarify factors affecting physical growth in children with primary VUR.Materials and Methods:The study was performed retrospectively in 260 primary VUR patients without chronic renal disease. Height and weight z-scores were calculated by anthropometric references in Turkish children and compared between patients grouped according to clinical properties.Results:Mean age of diagnosis was 43±4 months and mean duration of follow-up was 4.2±1.4 years. Mean height and weight z-scores of the 260 children were 0.22±0.96 and -0.11±1.0 at diagnosis; 0.14±0.97 and 0.01±1.3 at last visit respectively. Age at diagnosis, gender, grade, laterality and persistency of VUR had no impact on height and weight parameters. Although initial and final height z-scores were similar, we showed a higher height z-score improvement in patients with renal scarring and similarly in patients with surgery performed at least 6 months after the diagnosis. Mean final height and weight z-scores and weight z-score improvement were significantly lower in patients with urinary tract infections (UTIs) than in those without UTIs at follow-up. Further analysis concerning UTIs showed that final height z-scores were significantly lower in patients with afebrile UTIs at follow up, while it was similar between patients with and without febrile UTIs.Conclusion:The presence of renal scarring and UTIs at follow-up may lead to growth alterations in patients with primary VUR. Therefore, physicians and parents should be aware of UTI symptoms, even in the absence of fever, in pediatric VUR, thus preventing renal scarring and alterations in growth.